Efektivitas Penggunaan Wordwall dalam Model Game Based Learning terhadap Minat Belajar IPAS Siswa Sekolah Dasar - Fahria Zahra, Aprita; Muhisom; Wahyudi, Apri; Nurwahidin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning interest of fourth-grade students at SD Negeri 1 Labuhan Dalam. This study aims to determine the effect of using a game-based learning model based on a wordwall game on fourth-grade students' learning interest in science subjects at SD Negeri 1 Labuhan Dalam. The research method used is a quasi-experimental study with a nonequivalent control group design. The study population consisted of 89 students, and the sample was determined using a cluster random sampling technique. Data collection in this study involved observation, testing, and documentation. Data analysis prerequisite tests used normality and homogeneity tests. Hypothesis testing used simple linear regression. The results showed that the use of a game-based learning model based on a wordwall game had an effect on fourth-grade students' learning interest in science subjects at SD Negeri 1 Labuhan Dalam in the 2025/2026 academic year.